Estrategias de motivación y la participación activa en niños de la Institución Educativa Inicial N°390 Cochiquina, Pebas 2024 - Vasquez Yahuarcani, Nanci (2024)
The purpose of this research is to identify the relationship between the degree of implementation of motivational strategies and the active participation of children in the Initial Educational Institution N°390 Cochiquina, Pebas, during the year 2024. The research adopts a quantitative approach and is classified as relational. A non experimental design is employed, specifically with correlational cross-sectional designs. The study population consists of 121 children from the mentioned institution. For data collection, observation will be used as the technique and an observation guide as the instrument. The validity of this instrument will be evaluated by three specialists in the field, while reliability will be determined through the Alpha Cronbach test, conducted in a pilot test. The results of the Alpha Cronbach indicate a high Spearman correlation coefficient (0.815) and a significance value (p=0.05) suggesting that the observed relationship is statistically significant. Therefore, it is concluded that the null hypothesis is rejected and the general hypothesis is accepted, confirming that the implementation of motivational strategies is significantly related to the active participation of children in the study context.